1981
DOI: 10.1083/jcb.91.1.257
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a synaptic vesicle-specific membrane protein with a wide distribution in neuronal and neurosecretory tissue.

Abstract: Two different monoclonal antibodies, characterized initially as binding synaptic terminal regions of rat brain, bind a 65,000-dalton protein, which is exposed on the outer surface of brain synaptic vesicles . Immunocytochemical experiments at the electron microscope level demonstrate that these antibodies bind the vesicles in many different types of nerve terminals. The antibodies have been used successfully to purify synaptic vesicles from crude brain homogenates by immunoprecipitation onto the surface of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
251
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(262 citation statements)
references
References 48 publications
(56 reference statements)
8
251
1
2
Order By: Relevance
“…As shown in Figure 1d-g, the distribution of the two signals was identical, and both wild-type and mutant synaptotagmin were expressed almost exclusively at the plasma membrane. This intracellular sorting contrasts sharply with that normally seen in neurons and neuroendocrine cells, where synaptotagmin is delivered to synaptic vesicles and secretory granules, respectively (Matthew et al, 1981), but is in accord with the observed targeting of synaptotagmin to the plasma membrane in Chinese hamster ovary (CHO) cells (Jarousse & Kelly, 2001). We observed similar targeting using wild-type…”
Section: Resultssupporting
confidence: 48%
“…As shown in Figure 1d-g, the distribution of the two signals was identical, and both wild-type and mutant synaptotagmin were expressed almost exclusively at the plasma membrane. This intracellular sorting contrasts sharply with that normally seen in neurons and neuroendocrine cells, where synaptotagmin is delivered to synaptic vesicles and secretory granules, respectively (Matthew et al, 1981), but is in accord with the observed targeting of synaptotagmin to the plasma membrane in Chinese hamster ovary (CHO) cells (Jarousse & Kelly, 2001). We observed similar targeting using wild-type…”
Section: Resultssupporting
confidence: 48%
“…This protein is localized to synaptic vesicles and large dense core secretory vesicles (Matthew et al 1981). It spans the vesicle membrane once and has a short luminal domain and a large cytoplasmic region largely comprised of two C2 domains, designated C2A and C2B.…”
Section: Introductionmentioning
confidence: 99%
“…We used affinity purified polyclonal antibody against PI3K-C2␣ ( Arcaro et al, 2000), anti-hGH (Sigma), anti-Syt I (Matthew et al, 1981), anti-P18 (Wendler et al, 2001), anti-EEA1 (a kind gift from H.T. McMahon) and anti-clathrin heavy chain (Transduction Laboratories).…”
Section: Antibodiesmentioning
confidence: 99%